Application of an internet based, collaborative software environment in training and competition of top level beach volleyball - Link, D.; Lames, M. (International Journal of Computer Science in Sport, 2002)
During the last years, many methods for the genuine informational coupling of training and competition were suggested and applied to improve performance in sports. In the majority of cases, the systematic analysis of the own and the opponent`s technical and/or tactical skills, and conclusions on the training process, requires the physical presence of coaches at the competition location. In semi-professional sports, this "on the spot" service causes serious financial, logistical, and organisational problems due to restricted resources of players and federations. By using modem information and communication technology, these problems can be alleviated. The generic term groupware describes software systems, which support groups of geographically distributed people engaged with a common task, and provide an interface to a shared environment [ChuOl]. To enable the German top level beach volleyball teams to work collaboratively with their coaches via the internet, the university of Augsburg developed a groupware system, labelled VIAS v.4 (Video-Analysis-System) [LL02], which provides the following features: (a) video analysis of beach volleyball games based on a qualitative observation method [HL01]; (b) real-time video and audio conferencing; text messages for internet connections with poor bandwidth or high latency; (c) application viewing/ sharing by broadcasting analysis results, videos and mouse movements between two software instances; (d) specialized whiteboards and tactic charts to demonstrate player positions and their dynamic interaction. These key functions allow supplying players with relevant information all around the world. Taking advantage of a central reporting station, many teams could easily be equipped with scientific services without generating travelling expenses. The practical implementation of the developed software system will start in cooperation with the German beach volleyball teams, during their Olympic qualification in the summer 2003.